Ghrelin is present in human colostrum, transitional and mature milk - Aydin, S; Aydin, S; Ozkan, Y; Kumru, S (Elsevier Science Inc, 2006)
Ghrelin and its mRNA have recently been found in numerous human tissues including breast. The aim of this study was to compare the ghrelin levels in colostrum, mature and transitional milk and plasma in lactating women with plasma samples from non-lactating women. Venous blood samples were obtained from 17 healthy lactating women aged 22-35 years and from 16 age-matched controls. Colostrum, transitional and mature milk samples were collected just before suckling. The level of bioactive ghrelin was determined by RIA. Comparison of ghrelin values for lactating women showed significantly lower concentrations in colostrum (70.3 +/- 18 pg/ml), transitional milk (83.8 +/- 18 pg/ml) and mature milk (97.3 +/- 13 pg/ml) than in the corresponding plasma samples (first day 95 +/- 16 pg/ml, 10th day 111 +/- 13 pg/mI and 15th day 135 +/- 16 pg/ml). The plasma concentrations were lower in the lactating than in the non-lactating women. Thus, the ghrelin levels in colostrum, transitional and mature milk were elavated concomitantly with increasing plasma ghrelin after delivery. The origin of milk ghrelin is not known, but it probably comes from the plasma. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: ghrelin; mammalian milk; human colostrum, transitional and mature milk